2010
DOI: 10.1111/j.1440-1754.2010.01882.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in newborn sepsis in Sagamu, Nigeria: Bacterial aetiology, risk factors and antibiotic susceptibility

Abstract: The prevalence of sepsis was high in this cohort of high-risk infants. The low in vitro sensitivity of the leading microbes to commonly used drugs is challenging. Guidelines on the reduction of emergence of drug resistance must be provided and instituted in newborn units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 22 publications
5
57
1
1
Order By: Relevance
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 63%
“…The rates of sepsis in this study are comparable to those in units in Taiwan that reported rates ranging from 3% to 4% [18,19], but lower compared with data from other countries such as the Philippines, The Netherlands, and Nigeria, where sepsis rates have been reported to range from 15.1% to 19.6% [20][21][22]. Furthermore, at 2.68 cases per 1,000 live births, the rate of sepsis for inborn infants was lower than that reported in other countries including Korea (5.9 cases per 1,000 live births) [23], the USA (6.1 cases per 1,000 live births) [4], and India (14.8 cases per 1,000 live births) [24].…”
Section: Discussionsupporting
confidence: 63%
“…This is not unexpected, as Escherichia coli is a genital tract organism, which would likely be transmitted perinatally. Escherichia coli has not been as commonly reported as Klebsiella in Nigerian studies in recent times [9,13,18], but this may be because most studies did not differentiate between EOS and LOS. That no GBS was found in this study further buttresses the fact that it is not as common in this environment [10] as in developed countries, where it is the major cause of EOS [19,20].…”
Section: Discussionmentioning
confidence: 76%
“…Organisms causing EOS are usually maternally acquired before or during delivery, whereas organisms causing LOS are acquired from the environment, which could be the community or nosocomial in hospitalized patients [6]. Over the years, there have been increasing reports from developing countries, of changing patterns of the etiology of NNS [7][8][9]; however, these studies hardly diffentiated between EOS and LOS. The trend in etiology of EOS remains the same in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, over one decade the organisms causing neonatal sepsis had shifted from a predominance of gram negatives to gram positives. Previous studies have also established the predominance of gram positives in this decade (13)(14)(15)(16)(17). While bacteria are known to vary temporally, we postulate other reasons for this shift to more S. aureus in particular and consequently gram positive bacteria as a group; one postulate is that this may have resulted from a change in the type of bacteria colonizing the ano-genital region of the mother to mainly staphylococci and consequent newborn colonization with these organism; a future study assessing the maternal ano-genital colonization and newborn colonization with S aureus could answer this question.…”
Section: Discussionmentioning
confidence: 99%